A remark on the metric dimension in Riemannian manifolds of constant curvature - Shiva Heidarkhani Gilani; Reza Mirzaie; Ebrahim Vatandoost (AUT Journal of Mathematics and Computing)
We compute the metric dimension of Riemannian manifolds of constant curvature. We define the edge weghited metric dimension of the geodesic graphs in Riemannian manifolds and we show that each complete geodesic graph $G=(V,E)$ embedded in a Riemannian manifold of constant curvature resolves a totally geodesic submanifold of dimension $|V|-1$.